Functional Studies of Novel FOXL2 Variants in Chinese Families With Blepharophimosis–Ptosis–Epicanthus Inversus Syndrome - Li, Fang; Chen, Huifang; Wang, Yefei; Yang, Jie; Zhou, Yixiong; Song, Xin; Fan, Jiayan (Frontiers in Genetics, 2021)
Blepharophimosis-ptosis-epicanthus inversus syndrome (BPES) is a rare autosomal dominant disease mainly caused by FOXL2 variants. This genetic disorder is usually characterized by eyelid malformation and ovarian dysfunction. However, no reliable genotype/phenotype correlations have been established considering the ovarian phenotype. Here, we detected fifteen FOXL2 variants including 9 novel ones from seven families and eight sporadic cases, which expanded the spectrum of FOXL2 variants and identified a potential clinical cause. Functional studies, with respect to the effect of FOXL2 on the StAR promoter, showed that nonsense variants that lead to protein truncation before the polyalanine tract and missense variants (c.307C>T; p.(Arg103Cys), c.311A>C; p.(His104Pro), c.320G>A; p.(Ser107Asn) and c.335T>A; p.(Phe112Tyr)) within the central portion of the FOXL2 forkhead domain, significantly affect its suppressor activity. Such changes may explain the mechanism underlying a more severe phenotype, more likely to result in BPES type I. A luciferase reporter assay demonstrated that these variants significantly affect the suppressor activity of FOXL2 on StAR promoter. Furthermore, the missenses variants c.307C>T; p.(Arg103Cys), c.311A>C; p.(His104Pro), and c.320G>A; p.(Ser107Asn) were not able to transactivate OSR2, which is consistent with the eyelid malformation in these patients. The results from our cohort have expanded the spectrum of FOXL2 variants and have provided insights into genotype/phenotype correlations.